Recomendaciones para el diseño de cruces subfluviales para acueducto y sus obras asociadas (2018)
Currently many new water supply projects are being executed in Colombia. In this sense, the present work is concerned to recognize that sometimes the layout is in the obligation to cross a body of water or river, which requires the construction of a line under the water body, this with the object to alter the channel as little as possible and keep the banks protected. In the same way, this study is born of the need to respond to the question: what would be the best technology to use? Understanding that the stage of planning of the projects that are in the public procurement portal shows an absence of certainty of what technology should be used for the projects. The development of this research begins with an attempt to realize a typical profile of soil in the rivers of Colombia, finding a wide variety of geological formations that make up the national territory, which makes the entrusted task impossible. The following step consists in the collection and analysis of trenchless technologies named as: Horizontal Directional Drilling "HDD", Pipe Ramming, Auger Boring, Pipe Jacking and soil compaction methods. This analysis focuses on knowing the conditions under which these methods are most efficient and their limitations in terms of drilling lengths, diameters and soil types. A special chapter is devoted to the applicable types of pipe. Once the aspects relating to the state of the art have been clarified, an extensive analysis of the applicability of the different technologies is carried out based on key decision factors, which are the soil, the diameter of the pipe to be laid and the length of the crossing. Based on this analysis, a selection manual for the use of trenchless technology for subfluvial crossings is prepared and is put into practice in a real engineering example.